robots Evaluation of student performance in robotics with Arduino for interactive robot development - MILAGROS DEL CARMEN CASTAÑEDA BARBARAN (CLEI Electronic Journal)
Currently, robotics and technology are increasingly present in different areas of human development. New technologies are entering the field of education, where the student acquires and develops skills to solve solutions. This article presents the development of robotic prototype projects as an apprenticeship for higher education, in order for the student to develop didactic and playful activities, using low-cost robotics, thus encouraging creativity, logical thinking, robot programming, teamwork and problem solving. The methodology used was experimental through learning sessions in which 100 students participated, and a rubric and checklist were used for evaluation. Significant differences were obtained in the performance of the five groups when completing an activity. The calculated means showed on average, 10 students achieve the activity without help, 7.4 students achieve with minimal help and 2.6 students achieve with considerable help. It was concluded that the proposed learning was accepted by the students, and its application allowed detecting difficulties in the students when interacting with robotics and arduino.